Paradojas y dilemas de la participación social en la educación básica en México - Zurita Rivera, Úrsula (2013)
This article analyzes the promotion of social participation from the changes in educational policy due to the National Agreement for the Modernization of Basic Education, signed in 1992, focusing on social participation in the space of public policies, and in the process of social participation in the public schools of basic level. It was noted some institutionalization of the first dimension and a more irregular and vulnerable development in the second because of factors of diverse nature.